ANALYSIS OF THE MANAGEMENT OF VILLAGE OWNED ENTERPRISES (BUMDES) IN INCREASING THE INCOME OF THE COMMUNITY OF KUTA TRIENG VILLAGE, BIREUEN DISTRICT - Rahmatina; Rizki Ananda Saputra; Rizki Fitriah; Murni (Universitas Efarina, 2022)
This research aims to analyze how the management of Village-Owned Enterprises (Bumdes) Vaname Shrimp Benur increases community income. The aim of this research is to find out how Bumdes management increases the income of the people of Kuta Trieng Village. The type of research used in this research is descriptive qualitative, the data sources used are observation, interviews and documentation. And the data analysis techniques used include data redaction, data presentation and conclusions. Based on the research results, it shows that the management of the village-owned enterprise (BUMDes) Benur Udang Vaname, Kuta Trieng Village, in increasing income applies 5 principles of BUMDes management such as transparency, accountability, responsibility, professionalism and equality. With management principles, it can provide convenience for the community. Apart from that, BUMDes Benur Udang Vaname, Kuta Trieng Village also plays a role in developing and developing the economic potential of the Kuta Trieng village community to improve welfare and BUMDes also contributes fully as an alternative community income.